Corrosion of light powered Pt/TiO2 microrobots. (September 2020) - Maric, Tijana; Nasir, Muhammad Zafir Mohamad; Budanovic, Maja; Alduhaish, Osamah; Webster, Richard D.; Pumera, Martin
Highlights: Pt/TiO2 photo powered micromachines undergo corrosion. Pt/TiO2 loose ability to move under photocatalytic fuel-free mechanism due to corrosion. Pt/TiO2 remain active for H2 O2 bubble propulsion mechanism despite corrosion. Abstract: Catalytic light-powered microrobots have become a major focus in the current autonomous self-propelled micromotors research. The attractiveness of such machines stems from the fact that these motors are liquid "fuel-free", with their motion modulated by irradiation. It is assumed that as catalytic micro/nanoparticles, they can function eternally. We show here that Pt/TiO2 photo powered micromachines undergo corrosion and that they lose catalytic activity several days after deployment. Graphical abstract: Image, graphical abstract